Ein Vergleich kognitionsorientierter Stufenmodelle und ihrer normativen Implikationen für das interkulturelle und wertorientierte Lernen im Geographieunterricht - Applis, Stefan (Journal of Geography Education, 2015)
Intercultural learning is a central principle in the geography classroom. Existing theoretical concepts and their didactical operationalizations for the geography classroom however show substantial weaknesses. The paper contrasts the Development Model of Intercultural Sensitivity by Bennett and Hammer with step models of moral learning in the field of values-based learning. Moreover, its applicability for the construction of teaching and learning arrangements in the geography classroom is reflected.